2020
DOI: 10.1177/0967391120913658
|View full text |Cite
|
Sign up to set email alerts
|

Progress in polymer nanocomposites for bone regeneration and engineering

Abstract: The ultimate aim of tissue engineering entails fabrication of functional replacements for damaged organs or tissues. Scaffolds facilitate the proliferation of cells, while also improving their various functions. Scaffolds are 3-D structures capable of imitating mechanical and bioactive behaviors of tissues extracellular matrix, which provides enabling environment for cellular bonding, proliferation, and distinction. Hence, scaffolds are often applied in tissue engineering with the aim of facilitating damaged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(19 citation statements)
references
References 126 publications
0
16
0
1
Order By: Relevance
“… 10 , 47 , 48 These microfibers have a cotton candy like structure imitating a fibrin clot microstructure. 118 Human trials indicated that chronic wounds, such as diabetic foot ulcers and bedsores, healed in 6–10 weeks after application of Mirragen microfibers. 119 121 This technology is described to be an effective treatment for wounds which exhibit no healing with conventional treatment options.…”
Section: Applications Of Bbgsmentioning
confidence: 99%
“… 10 , 47 , 48 These microfibers have a cotton candy like structure imitating a fibrin clot microstructure. 118 Human trials indicated that chronic wounds, such as diabetic foot ulcers and bedsores, healed in 6–10 weeks after application of Mirragen microfibers. 119 121 This technology is described to be an effective treatment for wounds which exhibit no healing with conventional treatment options.…”
Section: Applications Of Bbgsmentioning
confidence: 99%
“…As bone matrix is a combination of organic (mainly collagen) and inorganic (apatite) composite materials, it seems logical to combine polymers and hydroxyapatite (HA) to develop scaffolds that meet all the desired requirements for bone applications [10][11][12][13][14][15]. HA is widely used in bone tissue engineering to enhance bioactivity, osteoconductivity, and osteoblast differentiation [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites with nano-sized carbonaceous fillers have attracted attention due to improvements in mechanical properties and conductivity when compared to the original polymer [9,10]. The development of well-dispersed graphene nanoparticles (GPN) in a polymeric matrix has opened a new and interesting topic in materials science [11].…”
Section: Introductionmentioning
confidence: 99%